Morphological and phylogenetic evidence reveal three new species of Aureoboletus (Boletaceae, Boletales) from China - Zhang, Xu; Tian, Run; Tang, Li-Ping; Liang, Zhi-Qun; Zhang, Wen-Hao; Jiang, Shuai; Wang, Cheng-Kai; Zeng, Nian-Kai (Phytotaxa, 2022)
Species of Aureoboletus (Boletaceae, Boletales) are diverse in China, and many taxa in the country have been described to date. Here, additional three new species, viz. A. guangdongensis, A. microcarpus, and A. rugosus are described based on morphology and molecular phylogenetic analyses of DNA sequences. Detailed descriptions, color photographs of fresh basidiomata, and line drawings of the microscopic features of the three new taxa are presented.